The Influence of Competence and Achievement Motivation on Teacher Performance - Wahyuningsih, Dian (Almana : Jurnal Manajemen dan Bisnis, 2023)
Teachers are one of the factors that determine the success of an education, and teacher performance needs to be considered properly. If the teacher's goals are achieved following the standards he has set, then the teacher's performance can be said to be high. If the teacher's performance is high, it will encourage success in carrying out the duties of a teacher. The purpose of this study was to determine the condition of competence, achievement motivation, and teacher performance at SMK Negeri 2 Baleendah. In addition, the purpose of this study was to determine the magnitude of the effect of competence, and achievement motivation on teacher performance at SMK Negeri 2 Baleendah. The method used in this study is a sample method where this study takes part of the 105 population teachers at SMK Negeri 2 Baleendah to become respondents. The data collected is by using a questionnaire. Questionnaires were distributed to 90 respondents and data processing from this study used path analysis. Competence at SMK Negeri 2 Baleendah is quite good. Likewise, achievement motivation at SMK Negeri 2 Baleendah is quite good and teacher performance at SMK Negeri 2 Baleendah is quite good, competence on teacher performance has a greater influence, and achievement motivation on teacher performance also has an influence. Competence and achievement motivation affect teacher performance.